2012
DOI: 10.1177/1066896912439095
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic Adenoma of the Urinary Tract

Abstract: Nephrogenic adenoma (NA) is an uncommon and intriguing lesion in the urinary tract. The pathogenesis of NA is not entirely clear. NA was considered to be a metaplastic process of the urothelium in response to chronic irritation of the urinary tract. However, recent evidence has shown that NA is not a metaplastic lesion but rather a proliferation of exfoliated and implanted renal epithelial cells in the urinary tract. Histologically, NAs exhibit, singly or in combination, tubules, small papillae, and microcysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 70 publications
2
15
0
3
Order By: Relevance
“…These immunohistochemical results are all in accordance with those previously reported in adult nephrogenic adenomas [13][14][15][16]. A study by Fromont and colleagues reported nonspecific positive staining for P504S and CDIO in nephrogenic adenomas as a result of the use of avidin-biotin detection procedure reacting with the high level of endogenous biotin [14].…”
Section: Discussionsupporting
confidence: 93%
“…These immunohistochemical results are all in accordance with those previously reported in adult nephrogenic adenomas [13][14][15][16]. A study by Fromont and colleagues reported nonspecific positive staining for P504S and CDIO in nephrogenic adenomas as a result of the use of avidin-biotin detection procedure reacting with the high level of endogenous biotin [14].…”
Section: Discussionsupporting
confidence: 93%
“…They are rarely a challenge for the experienced pathologist [8]. On the other hand, nephrogenic adenoma ( Figure B-D), a relatively uncommon lesion induced by chronic irritation of the urothelial mucosa, is a benign entity and a common mimic of adenocarcinoma [8,9]. We collected 5 cases each from von Brunn nests, cystitis glandularis, and cystitis cystica as well as 10 cases of nephrogenic adenoma.…”
Section: Telomerase Reverse Transcriptase Promoter Mutation In Benignmentioning
confidence: 96%
“…[3,9,11] Histopathological study is needed to distinguish it from malignancy. [12] NA generally demonstrates multiple histologic patterns, with a minority composing of small tubules or papillary projections alone. Small tubules are often surrounded by a thickened hyalinized basement membrane without any desmoplastic stromal response.…”
Section: Discussionmentioning
confidence: 99%
“…Small tubules are often surrounded by a thickened hyalinized basement membrane without any desmoplastic stromal response. [12,13] Treatment of intravesical lesions consists of TUR and fulguration and rarely partial or total cystectomy may be required after ineffective TUR. [3,14] In our case patient underwent open submucosal resection and fulguration.…”
Section: Discussionmentioning
confidence: 99%